2017
DOI: 10.1002/2211-5463.12162
|View full text |Cite
|
Sign up to set email alerts
|

AZD0530 sensitizes drug‐resistantALK‐positive lung cancer cells by inhibitingSRCsignaling

Abstract: Most tumors develop resistance to targeted cancer drugs, even though these drugs have produced substantial clinical responses. Here we established anaplastic lymphoma kinase (ALK)‐positive drug‐resistant lung cancer cell lines, which are resistant to ceritinib (LDK378). We found that ceritinib treatment resulted in robust upregulation of SRC activity, as measured by the phosphorylation of the SRC substrate paxillin. Knockdown of SRC alone with siRNA effectively sensitized ceritinib resistance in ALK‐positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…For example, AXL , a druggable kinase implicated as a resistance driver for many targeted therapies (Liu et al, 2009; Zhang et al, 2012), has significant negative CARE scores for multiple compounds screened in three cohorts (Figure 2A, B). Another example is that SRC has negative CARE scores on most drugs (Figure 2A, C), which corroborates previous findings that SRC activation promotes resistance towards several targeted therapies (Wilson et al, 2014; Zhao et al, 2017). In contrast, CSK , a negative regulator of SRC (Okada et al, 1991), has significant positive CARE scores for many compounds (Figure 2C), suggesting that loss of CSK may promote drug resistance towards many targeted therapies.…”
Section: Resultssupporting
confidence: 89%
“…For example, AXL , a druggable kinase implicated as a resistance driver for many targeted therapies (Liu et al, 2009; Zhang et al, 2012), has significant negative CARE scores for multiple compounds screened in three cohorts (Figure 2A, B). Another example is that SRC has negative CARE scores on most drugs (Figure 2A, C), which corroborates previous findings that SRC activation promotes resistance towards several targeted therapies (Wilson et al, 2014; Zhao et al, 2017). In contrast, CSK , a negative regulator of SRC (Okada et al, 1991), has significant positive CARE scores for many compounds (Figure 2C), suggesting that loss of CSK may promote drug resistance towards many targeted therapies.…”
Section: Resultssupporting
confidence: 89%
“…Masitinib, another SFK tyrosine kinase inhibitor, was assessed in a randomized controlled open-label trail, and showed that masitinib generated a statistically signi cant survival bene t over standard of care in advanced gastrointestinal stromal tumor [30]. Saracatinib (AZD0530) targets Fyn and inhibits the growth of lung cancer cells that are resistant to ALK inhibitors [31], interestingly, this compound also suppresses Fyn induced invasion and metastasis by decreasing Vimentin and Snail [32]. However, subsequent studies showed that saracatinib inhibits other SFKs kinase activities, such as Src, Yes, and Lyn.…”
Section: Discussionmentioning
confidence: 99%
“…Masitinib, another SFK tyrosine kinase inhibitor, was assessed in a small phase II clinical trial for AD, ameliorated cognitive function and activities of daily living [28]. Saracatinib (AZD0530) targets Fyn and inhibits the growth of lung cancer cells that are resistant to ALK inhibitors [29], interestingly, this compound also suppresses Fyn induced invasion and metastasis by decreasing Vimentin and Snail [30]. However, subsequent studies showed that saracatinib inhibits other SFKs kinase activities, such as Src, Yes, and Lyn.…”
Section: Discussionmentioning
confidence: 99%